Multi–functional intramedullary self-locking ulna nailing system: Proximal oblique locking without the need of fluoroscopic guidance, and it’s effects on olecranon joint surface (Annals of Medical Research, 2021)
Aim: Due to the necessity of using the small diameter nails in the ulna, negative outcomes such as failure in the self-locking, long term exposure to radiation, and increased operation time are expected. Several clinical trials propose that an ideal nail system for unlar fixation challenge has not been developed yet. Material and Methods: This study involved the use of a new multifunctional intramedullary self-locking ulna nailing system and 36 intact dry cadaveric ulna bones. The relationship between the oblique self-locking screw, which has made a crucial contribution to the nailing system, and the joint surface of olecranon was investigated because this screw does not necessitate the use of fluoroscopic guidance and is easy to apply.Results: In our study, during anterior or medial or posterior oblique locking, no olecranon joint surface damage occurred on any bone with a locking rate of 100%. Conclusion: The clinical trials demonstrated that the proximal oblique locking was achieved easily in a short period of time, indicating the device’s immense value for the patient and the surgeon.
Keywords: Intramedullary nail; olecranon; self-locking screw